Atrial fibrillation and cancer – An unexplored field in cardiovascular oncology. (May 2019) - Chu, Gordon; Versteeg, Henri H.; Verschoor, Arie J.; Trines, Serge A.; Hemels, Martin E.W.; Ay, Cihan; Huisman, Menno V.; Klok, Frederikus A.
Abstract: An increasing body of evidence suggests an association between cancer and atrial fibrillation (AF). The exact magnitude and underlying mechanism of this association are however unclear. Cancer-related inflammation, anti-cancer treatment and other cancer-related comorbidities are proposed to affect atrial remodelling, increasing the susceptibility of cancer patients for developing AF. Moreover, cancer is assumed to modify the risk of thromboembolisms and bleeding. A thorough and adequate understanding of these risks is however lacking, as current literature is scarce and show ambiguous results in AF patients. The standardized risk-models that normally aid the clinician in the decision of initiating anticoagulant therapy do not take the presence of malignancy into account. Other factors that complicate risk assessment in AF patients with cancer include drug-drug interactions and other cancer-related comorbidities such as renal impairment. In this review, we highlight the available literature regarding epidemiological association, risk assessment and anticoagulation therapy in AF patients with cancer.